2021
DOI: 10.3892/mmr.2021.12510
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA KCNQ1OT1 may function as a competitive endogenous RNA in atrial fibrillation by sponging miR‑223‑3p

Abstract: Atrial fibrillation (AF) is one of the most common forms of cardiac arrhythmia. Novel evidence has indicated that a competing endogenous RNA (ceRNA) mechanism may occur in AF. The present study aimed to identify differentially expressed microRNAs (miRNAs/miRs) in AF and predict their targeting long non-coding RNAs (lncRNAs) to identify a potential ceRNA network involved in AF using bioinformatics analysis. The GSE68475 microarray dataset was downloaded from the Gene Expression Omnibus database and differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…According to the literature, lncRNA KCNQ1OT1 has also been proven to be involved in the progression of multiple diseases, such as osteolysis ( 47 ), fracture healing ( 48 ), myocardial ischemia/reperfusion injury ( 49 ), atrial fibrillation ( 50 ), and diabetic cardiomyopathy ( 51 ). Furthermore, research has shown that lncRNA KCNQ1OT1 is also related to the progression of acute promyelocytic leukemia ( 52 ), ovarian cancer ( 17 ), bladder cancer ( 53 ), and NSCLC ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, lncRNA KCNQ1OT1 has also been proven to be involved in the progression of multiple diseases, such as osteolysis ( 47 ), fracture healing ( 48 ), myocardial ischemia/reperfusion injury ( 49 ), atrial fibrillation ( 50 ), and diabetic cardiomyopathy ( 51 ). Furthermore, research has shown that lncRNA KCNQ1OT1 is also related to the progression of acute promyelocytic leukemia ( 52 ), ovarian cancer ( 17 ), bladder cancer ( 53 ), and NSCLC ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lncRNAs can target several miRNAs and the lncRNA-miRNA network serves a crucial role in tumors [ 28 , 29 ]. For instance, linc00337 expression increases in lung adenocarcinoma, while its knockdown in cell lines could suppress cellular activities by targeting miR-1285-3p [ 27 ].…”
Section: Discussionmentioning
confidence: 99%